2016
DOI: 10.1161/circulationaha.116.024441
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Wnt Inhibitors IGFBP-4 and Dkk1 in Cardiac Ischemia by Differential Targeting of LRP5/6 and β-catenin

Abstract: Our findings reveal previously unidentified dual roles of LRP5/6 involved in the cardiomyocyte response to ischemic injury. These findings suggest new therapeutic strategies in ischemic heart disease by fine-tuning LRP5/6 and β-catenin signaling within the Wnt/β-catenin pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 57 publications
4
60
0
Order By: Relevance
“…IGFBP-4 acted as a cardiogenic growth factor by inhibiting Wnt signalling 449 (Zhu, et al 2008), and it induced cardiomyocyte differentiation from stem cells by inhibiting β-450 catenin signalling (Xue, et al 2014). IGFBP-4 injection in rats also decreased ischaemic injury after 451 myocardial infarction by inhibiting β-catenin activation (Wo, et al 2016). A number of other 452 studies also suggested IGF-independent actions of IGFBP-4 but the underlying mechanisms were 453 not studied (Perks, et al 1999;Singh, et al 1994;Wright, et al 2002).…”
Section: Igf-independent Actions 447mentioning
confidence: 97%
“…IGFBP-4 acted as a cardiogenic growth factor by inhibiting Wnt signalling 449 (Zhu, et al 2008), and it induced cardiomyocyte differentiation from stem cells by inhibiting β-450 catenin signalling (Xue, et al 2014). IGFBP-4 injection in rats also decreased ischaemic injury after 451 myocardial infarction by inhibiting β-catenin activation (Wo, et al 2016). A number of other 452 studies also suggested IGF-independent actions of IGFBP-4 but the underlying mechanisms were 453 not studied (Perks, et al 1999;Singh, et al 1994;Wright, et al 2002).…”
Section: Igf-independent Actions 447mentioning
confidence: 97%
“…The canonical Wnt/β-catenin signaling is negatively regulated by a range of molecules, which act either extracellularly by affecting the interaction between Wnt ligands and its receptor complex, or intracellularly by interfering with signal transduction (Chen et al, 2009; Paluszczak et al, 2015; Wo et al, 2016). Dkk1 has been regarded as one of the extracellular antagonist of canonical Wnt/β-catenin signaling (Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the LRP coreceptors in infarct healing has been studied more extensively. Induction of MI in mice deficient in LRP5 resulted in an increase in infarct size (Borrell-Pages et al, 2016) but no change in infarct area or cardiac function, as observed when LRP5 was specifically deleted in CMs (Wo et al, 2016). In several studies, the effect of DKK proteins, endogenous antagonists of LRP proteins, on infarct healing was addressed.…”
Section: Wnt Signalingmentioning
confidence: 99%